On Terms: Maladaptive Behavior - Donald, Courtney (Journal of Verbal Behavior, 2026)
There is no shortage of terms that are used to describe and articulate the strategies, practices, and underpinnings associated with the work engaged in by behavior analysis. Two terms that a clinic-focused behavior analyst may hear often are maladaptive behavior and problem behavior. These terms are not only common within our everyday practice, but they are also peppered throughout behavioral literature. Despite their permanency in the behavior analyst's repertoire, their meanings remain inconsistent, interchangeable, and conceptually unclear. For over a century, this lack of precision has gone unchecked, despite extensive research on undesirable or clinically significant behaviors. This article offers individuals a recount of the history, definitional limitations, and functional implications of these terms. From the perspective of early psychological scholarship and contemporary behavior-analytic sources, I argue that the field of Applied Behavior Analysis (ABA) will benefit from distinguishing maladaptive behavior as the presence of behavior that adversely affects the individual, while problem behavior should refer to the absence or inhibition of adaptive responses in relation to others' social behaviors. Furthermore, I propose that both terms be used to describe the effects on the person engaging in the behavior, instead of others around the individual, as a method of improving directionality and functional clarity. As a field focused on verbal behavior, becoming more conceptually precise with our own verbal behavior will lead to a more coherent basis for interpreting and treating behaviors that interfere with individuals' adaptation and well-being.
Keywords: maladaptive behavior; problem behavior; behavioral terminology; verbal behavior